PRAKTIK JUAL BELI MENANG ARISAN DALAM MADZHAB SYAFI’I (Studikasus di DesaBanyuputihKecamatanBanyuputih KabupatenSitubondo) - Jonwari (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2021)
Buying and selling to win arisan is a type of arisan that uses the lottery method at a time that has been determined or agreed upon by all arisan members. However, with the passage of time human needs change. This is because of the fulfillment of needs that must be met immediately, thus making some people try to get money in a fast and easy way to go. By practicing buying and selling, winning the social gathering is one way to meet needs. Based on the results of this study, it can be seen that the practice of buying and selling social gathering wins with the lottery method that occurs in Banyuputih Village, Banyuputih Subdistrict, there is an additional payment without any agreement. According to the Shafi'i madhhab, additional payments that occur in the sale and purchase of winning social gatherings are legal, because the additional payment is a form of gratitude to the seller for wanting to help in trouble. In buying and selling transactions, the social gathering is based on the principles of consensual and mutual help and in accordance with sharia law.